"Toronto Has No History!" Indigeneity, Settler Colonialism, and Historical Memory in Canada's Largest City - Freeman, Victoria Jane
The Indigenous past is largely absent from settler representations of the history of the city of Toronto, Canada. Nineteenth and twentieth century historical chroniclers often downplayed the historic presence of the Mississaugas and their Indigenous predecessors by drawing on doctrines of terra nullius, ignoring the significance of the Toronto Purchase, and changing the city’s foundational story from the establishment of York in 1793 to the incorporation of the City of Toronto in 1834. These chroniclers usually assumed that “real Indians” and urban life were inimical. Often their representations implied that local Indigenous peoples had no significant history and thus the region had little or no history before the arrival of Europeans. Alternatively, narratives of ethical settler indigenization positioned the Indigenous past as the uncivilized starting point in a monological European theory of historical development. In many civic discourses, the city stood in for the nation as a symbol of its future, and national history stood in for the region’s local history. The national replaced ‘the Indigenous’ in an ideological process that peaked between the 1880s and the 1930s. Concurrently, the loyalist Six Nations were often represented as the only Indigenous people with ties to Torontonians, while the specific historical identity of the Mississaugas was erased. The role of both the government and local settlers in crowding the Mississaugas out of their lands on the Credit River was rationalized as a natural process, while Indigenous land claims, historical interpretations, and mnemonic forms were rarely accorded legitimacy by non-Indigenous city residents. After World War II, with new influxes of both Indigenous peoples and multicultural immigrants into the city, colonial narratives of Toronto history were increasingly challenged and replaced by multiple stories or narrative fragments. Indigenous residents created their own representations of Toronto as an Indigenous place with an Indigenous history; emphasizing continuous occupation and spiritual connections between place and ancestors. Today, contention among Indigenous groups over the fairness of the Mississauga land claim, epistemic differences between western and Indigenous conceptions of history, and ongoing settler disavowal of the impact of colonialism have precluded any simple or consensual narrative of Toronto’s past. PhD